Survey shows marked variations in approaches to redirection of care for critically ill very preterm infants in 11 countries. (14th November 2019) - Helenius, Kjell; Morisaki, Naho; Kusuda, Satoshi; Shah, Prakesh S.; Norman, Mikael; Lehtonen, Liisa; Reichman, Brian; Darlow, Brian A.; Noguchi, Akihiko; Adams, Mark; Bassler, Dirk; Håkansson, Stellan; et al.
Abstract: Aim: We surveyed care practices for critically ill very preterm infants admitted to neonatal intensive care units (NICUs) in the International Network for Evaluating Outcomes in Neonates (iNeo) to identify differences relevant to outcome comparisons. Methods: We conducted an online survey on care practices for critically ill very preterm infants and infants with severe intracranial haemorrhage (ICH). The survey was distributed in 2015 to representatives of 390 NICUs in 11 countries. Survey replies were compared with network incidence of death and severe ICH for infants born between 23 0/7 and 28 6/7 weeks of gestation from January 1, 2015, to December 31, 2015. Results: Most units in Israel, Japan and Tuscany, Italy, favoured withholding care when care was considered futile, whereas most units in other networks favoured redirection of care. For infants with bilateral grade 4 ICH, redirection of care was very frequently (≥90% of cases) offered in the majority of units in Australia and New Zealand and Switzerland, but rarely in other networks. Networks where redirection of care was frequently offered for severe ICH had lower rates of survivors with severe ICH. Conclusion: We identified marked inter‐network differences in care approaches that need to be considered when comparing outcomes.